A high-flux, anti-pollution inorganic special membrane and its preparation process
A protective impregnation process for ceramic membranes using a solution of ammonia water, ethanol, deionized water, polyethylene glycol, modified β-cyclodextrin, and composite fiber nanocrystals addresses flux decay issues, resulting in a high-flux, antibacterial, and anti-pollution membrane with enhanced durability.
Patent Information
- Application Number
- CN202411187946.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-28
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-08-28
AI Technical Summary
Ceramic membranes suffer from rapid flux decay due to biological and organic contamination, leading to reduced separation efficiency and shortened service life.
A process involving a protective impregnation solution with ammonia water, ethanol, deionized water, polyethylene glycol, modified β-cyclodextrin, dopamine hydrochloride, and composite fiber nanocrystals is used to treat ceramic membranes, forming a protective layer that enhances flux and provides antibacterial and anti-pollution properties through a self-repairing mechanism.
The resulting inorganic special membrane maintains high flux and exhibits long-lasting antibacterial and anti-fouling properties, improving separation efficiency and extending the membrane's service life.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the field of membrane separation, in particular to a high-flux, pollution-resistant inorganic special membrane and a preparation process thereof. Background Art
[0002] In modern society, membrane separation is widely used in the fields of drinking water production, wastewater treatment and recycling, seawater desalination, etc. Especially in the field of ultrafiltration, polymer ultrafiltration membranes have attracted widespread attention because of their easy processing, recyclability and good separation properties.
[0003] Ceramic membrane is a common inorganic separation membrane. Compared with organic polymer membrane, it has higher mechanical properties, thermal stability and chemical stability. However, during the use of ceramic membrane, biological and organic contamination can easily cause its flux to decay rapidly, thereby reducing the separation efficiency and shortening the membrane service life. Summary of the invention
[0004] The purpose of the present invention is to provide a high-flux, anti-pollution inorganic special membrane and a preparation process thereof to solve the problems in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] A process for preparing a high-flux, anti-pollution inorganic special membrane comprises the following steps:
[0007] S1: washing the ceramic membrane to obtain a pretreated ceramic membrane;
[0008] S2: preparing a protective impregnation solution using ammonia water, ethanol, deionized water, polyethylene glycol, modified β-cyclodextrin, dopamine hydrochloride, and composite fiber nanocrystals;
[0009] S3: The pretreated ceramic membrane is transferred to a protective impregnation solution, ultrasonically vibrated, and dried to obtain a high-flux, anti-pollution inorganic special membrane.
[0010] Furthermore, the working condition of ultrasonic oscillation is: time is 10-15min.
[0011] Furthermore, the preparation of the protective impregnation liquid includes the following steps: mixing ammonia water, ethanol and deionized water, stirring at 18-25°C for 20-30 minutes, adding polyethylene glycol, adding a mixture of dopamine hydrochloride and deionized water, adding a mixture of composite fiber nanocrystals, modified β-cyclodextrin and deionized water, and ultrasonically stirring for 20-30 minutes to obtain a protective impregnation liquid.
[0012] Furthermore, the mass ratio of polyethylene glycol, dopamine hydrochloride, composite fiber nanocrystals, and modified β-cyclodextrin is 2:2.5:(0.3-0.5):5.
[0013] Further, the preparation of composite fiber nanocrystals includes the following steps:
[0014] 1) Mix the fiber nanocrystals and deionized water, perform ultrasonic treatment for 20-30 minutes, heat to 20-30°C, add titanium tetrachloride, keep warm for 40-60 minutes, cool, centrifuge, wash, dry and grind to obtain modified fiber nanocrystals;
[0015] 2) Mix hydroquinone acrylamide, modified fiber nanocrystals and N,N-dimethylformamide, heat to 98-102°C, stir for 1-2h, add 3-acrylamidophenylboronic acid, keep warm for 8-10min, add azobisisobutyronitrile, keep warm for 2-3h to obtain composite fiber nanocrystals.
[0016] Further, the preparation of modified β-cyclodextrin comprises the following steps:
[0017] (1) β-cyclodextrin and NaOH solution were mixed, p-toluenesulfonyl chloride and acetonitrile were added, stirring was continued for 2-3 hours, vacuum-filtered, the pH of the solution was adjusted to 2, and the solution was kept warm at 3°C for 10-12 hours, vacuum-filtered, dried, and recrystallized. Boiling distilled water was added until dissolved, cooled, vacuum-filtered, and dried to obtain mono-(6-O-p-methylbenzenesulfonyl)-β-cyclodextrin;
[0018] (2) Mix mono-(6-O-toluenesulfonyl)-β-cyclodextrin and diallylamine, heat to 78-82°C in a water bath for 4-5 hours, cool, add methanol and acetonitrile in sequence, filter, and dry to obtain vinylated β-cyclodextrin;
[0019] (3) Vinylated β-cyclodextrin, hydroquinone acrylamide and N,N-dimethylformamide are mixed and kept warm for 1-2 hours, azobisisobutyronitrile is added, and the temperature is raised to 60-80°C and kept warm for 2-3 hours to obtain modified β-cyclodextrin.
[0020] Furthermore, the mass ratio of hydroquinone acrylamide, composite fiber nanocrystals, and 3-acrylamidophenylboric acid is 2.2:5:1.8.
[0021] Furthermore, the mass ratio of vinylated β-cyclodextrin to hydroquinone acrylamide is 5:1.
[0022] Further, the preparation of hydroquinone acrylamide comprises the following steps:
[0023] Mix hydroquinone, N-hydroxymethyl acrylamide and anhydrous ethanol, heat to 30-35°C, add concentrated sulfuric acid, keep warm for 8 days, let stand for 1 day, filter and wash until neutral, recrystallize with anhydrous ethanol 3-5 times, and dry to obtain hydroquinone acrylamide.
[0024] Beneficial effects of the present invention:
[0025] The present invention provides a high-flux, anti-pollution inorganic special membrane and its preparation process, including a ceramic membrane and a protective layer formed on the surface of the ceramic membrane by a protective impregnation liquid, so that the prepared inorganic special membrane has high flux and a self-repairing green, antibacterial and anti-pollution surface.
[0026] The present invention selects bio-based raw materials such as dopamine hydrochloride, fiber nanocrystals, and beta-cyclodextrin as raw materials to construct a protective impregnation solution; in order to give the ceramic membrane the ability to photodegrade pollutants, titanium tetrachloride is used to in-situ generate titanium dioxide on the surface of the fiber nanocrystals to obtain modified fiber nanocrystals; in order to improve the uniformity of dispersion of the fiber nanocrystals in the protective impregnation solution, hydroquinone acrylamide with anti-fouling and antibacterial effects is attached to the modified fiber nanocrystals by using the hydroxyl groups on the surface thereof, and then 3-acrylamide phenylboronic acid is continuously grafted by free radical reaction to obtain composite fiber nanocrystals; the boric acid group on the composite fiber nanocrystals and the polyethylene glycol in the protective impregnation solution have a dynamic borate ester bond, so as to give the protective layer a certain self-repairing ability, thereby improving the long-lasting antibacterial and anti-fouling properties of the inorganic special membrane.
[0027] β-cyclodextrin is introduced into the protective impregnation liquid to further improve the stability of the protective layer. In order to improve the uniformity of the dispersion of β-cyclodextrin in the protective impregnation liquid, a multiple interpenetrating cross-linked network of β-cyclodextrin, polydopamine and polyethylene glycol is constructed to further improve the self-repairing ability of the protective layer and the adhesion of the protective impregnation liquid to the ceramic membrane. Mono-(6-O-p-methylbenzenesulfonyl)-β-cyclodextrin is synthesized using β-cyclodextrin as raw material, and then vinylized with diallylamine to obtain vinylated β-cyclodextrin. Then, free radical reaction is used to continue to graft hydroquinone acrylamide with anti-fouling and antibacterial effects to give it permanent antibacterial and anti-fouling properties, thereby significantly improving the anti-fouling and separation selectivity of the inorganic special membrane and broadening the scope of application of the inorganic special membrane. DETAILED DESCRIPTION
[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] It should be noted that if the embodiments of the present invention involve directional indications such as up, down, left, right, front, and back, the directional indication is only used to explain a specific posture such as the relative position relationship between the components, the movement status, etc. If the specific posture changes, the directional indication will also change accordingly. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in this field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the protection scope required by the present invention.
[0030] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.
[0031] Example 1: A process for preparing a high-flux, anti-pollution inorganic special membrane, comprising the following steps:
[0032] S1: washing the ceramic membrane to obtain a pretreated ceramic membrane;
[0033] The working conditions of ultrasonic oscillation are: time is 10min;
[0034] S2: preparing an antifouling impregnation solution using ammonia water, ethanol, deionized water, polyethylene glycol, modified β-cyclodextrin, dopamine hydrochloride, and composite fiber nanocrystals;
[0035] The preparation of the antifouling impregnation liquid comprises the following steps: 2 mL of ammonia water, 20 mL of ethanol, and 45 mL of deionized water are mixed, stirred at 18° C. for 30 min, 2 g of polyethylene glycol is added, a mixed solution of 2.5 g of dopamine hydrochloride and 5 mL of deionized water is added, 0.3 g of composite fiber nanocrystals, 5 g of modified β-cyclodextrin, and 10 mL of deionized water is added, and ultrasonic stirring is performed for 20 min to obtain the antifouling impregnation liquid;
[0036] The preparation of the composite fiber nanocrystal comprises the following steps:
[0037] 1) 0.1 g of fiber nanocrystals and 100 mL of deionized water were mixed, ultrasonically treated for 20 min, heated to 20 °C, 3 mL of titanium tetrachloride was added, and the mixture was kept warm for 60 min. The modified fiber nanocrystals were obtained by cooling, centrifugation, washing, drying, and grinding.
[0038] 2) Mix 2.2 g of hydroquinone acrylamide, 5 g of composite fiber nanocrystals, and 20 mL of N,N-dimethylformamide, heat to 98 °C, stir for 2 h, add 1.8 g of 3-acrylamidophenylboronic acid, keep warm for 8 min, add 0.04 g of azobisisobutyronitrile, keep warm for 2 h, and obtain composite fiber nanocrystals;
[0039] The preparation of the modified β-cyclodextrin comprises the following steps:
[0040] (1) 17.2 g of β-cyclodextrin and 200 mL of 1% NaOH solution were mixed, 2.9 g of p-toluenesulfonyl chloride and 11 mL of acetonitrile were added, stirring was continued for 2 h, vacuum filtered, the pH of the solution was adjusted to 2, and the solution was kept warm at 3 °C for 10 h, vacuum filtered, dried, and recrystallized. Boiling distilled water was added until dissolved, cooled, vacuum filtered, and dried to obtain mono-(6-O-p-methylbenzenesulfonyl)-β-cyclodextrin;
[0041] (2) Mix 4 g of mono-(6-O-toluenesulfonyl)-β-cyclodextrin and 0.7 mol of diallylamine, heat to 78 °C in a water bath for 5 h, cool, add 40 mL of methanol and 240 mL of acetonitrile, filter and dry to obtain vinylated β-cyclodextrin;
[0042] (3) 5 g of vinylated β-cyclodextrin, 1 g of hydroquinone acrylamide, and 20 mL of N,N-dimethylformamide were mixed, kept warm for 1 h, 0.03 g of azobisisobutyronitrile was added, and the temperature was raised to 60 °C and kept warm for 3 h to obtain modified β-cyclodextrin;
[0043] The preparation of the hydroquinone acrylamide comprises the following steps:
[0044] 2mmol hydroquinone, 1mmol N-hydroxymethyl acrylamide, and 500mL anhydrous ethanol were mixed, heated to 30°C, 30mL concentrated sulfuric acid was added, the mixture was kept warm for 8 days, allowed to stand for 1 day, filtered and washed until neutral, recrystallized with anhydrous ethanol for 3 times, and dried to obtain hydroquinone acrylamide;
[0045] S3: The pretreated ceramic membrane is transferred to an anti-fouling impregnation solution, ultrasonically vibrated, and dried to obtain a high-flux, anti-fouling inorganic special membrane.
[0046] Example 2: A process for preparing a high-flux, anti-pollution inorganic special membrane, comprising the following steps:
[0047] S1: washing the ceramic membrane to obtain a pretreated ceramic membrane;
[0048] The working conditions of ultrasonic oscillation are: time is 12min;
[0049] S2: preparing an antifouling impregnation solution using ammonia water, ethanol, deionized water, polyethylene glycol, modified β-cyclodextrin, dopamine hydrochloride, and composite fiber nanocrystals;
[0050] The preparation of the antifouling impregnation liquid comprises the following steps: 2 mL of ammonia water, 20 mL of ethanol, and 45 mL of deionized water are mixed, stirred at 20° C. for 25 min, 2 g of polyethylene glycol is added, a mixed solution of 2.5 g of dopamine hydrochloride and 5 mL of deionized water is added, 0.4 g of composite fiber nanocrystals, 5 g of modified β-cyclodextrin, and 10 mL of deionized water is added, and ultrasonic stirring is performed for 25 min to obtain the antifouling impregnation liquid;
[0051] The preparation of the composite fiber nanocrystal comprises the following steps:
[0052] 1) 0.1 g of fiber nanocrystals and 100 mL of deionized water were mixed, ultrasonically treated for 25 min, heated to 25 °C, 3 mL of titanium tetrachloride was added, and the mixture was kept warm for 50 min. The mixture was cooled, centrifuged, washed, dried, and ground to obtain modified fiber nanocrystals.
[0053] 2) Mix 2.2 g of hydroquinone acrylamide, 5 g of composite fiber nanocrystals, and 20 mL of N,N-dimethylformamide, heat to 100 °C, stir for 1.5 h, add 1.8 g of 3-acrylamidophenylboronic acid, continue to heat for 9 min, add 0.04 g of azobisisobutyronitrile, and heat for 2.5 h to obtain composite fiber nanocrystals;
[0054] The preparation of the modified β-cyclodextrin comprises the following steps:
[0055] (1) 17.2 g of β-cyclodextrin and 200 mL of 1% NaOH solution were mixed, 2.9 g of p-toluenesulfonyl chloride and 11 mL of acetonitrile were added, stirring was continued for 2.5 h, vacuum filtered, the pH of the solution was adjusted to 2, and the solution was kept at 3 °C for 11 h, vacuum filtered, dried, and recrystallized. Boiling distilled water was added until dissolved, cooled, vacuum filtered, and dried to obtain mono-(6-O-p-methylbenzenesulfonyl)-β-cyclodextrin;
[0056] (2) Mix 4 g of mono-(6-O-toluenesulfonyl)-β-cyclodextrin and 0.7 mol of diallylamine, heat to 80°C in a water bath for 4.5 h, cool, add 40 mL of methanol and 240 mL of acetonitrile, filter, and dry to obtain vinylated β-cyclodextrin;
[0057] (3) 5 g of vinylated β-cyclodextrin, 1 g of hydroquinone acrylamide, and 20 mL of N,N-dimethylformamide were mixed, kept warm for 1.5 h, 0.03 g of azobisisobutyronitrile was added, and the temperature was raised to 70 °C and kept warm for 2.5 h to obtain modified β-cyclodextrin;
[0058] The preparation of the hydroquinone acrylamide comprises the following steps:
[0059] 2mmol hydroquinone, 1mmol N-hydroxymethyl acrylamide, and 500mL anhydrous ethanol were mixed, heated to 33°C, 30mL concentrated sulfuric acid was added, the mixture was kept warm for 8 days, allowed to stand for 1 day, filtered and washed until neutral, recrystallized with anhydrous ethanol for 4 times, and dried to obtain hydroquinone acrylamide;
[0060] S3: The pretreated ceramic membrane is transferred to an anti-fouling impregnation solution, ultrasonically vibrated, and dried to obtain a high-flux, anti-fouling inorganic special membrane.
[0061] Example 3: A process for preparing a high-flux, anti-pollution inorganic special membrane, comprising the following steps:
[0062] S1: washing the ceramic membrane to obtain a pretreated ceramic membrane;
[0063] The working conditions of ultrasonic oscillation are: time is 15min;
[0064] S2: preparing an antifouling impregnation solution using ammonia water, ethanol, deionized water, polyethylene glycol, modified β-cyclodextrin, dopamine hydrochloride, and composite fiber nanocrystals;
[0065] The preparation of the antifouling impregnation liquid comprises the following steps: 2 mL of ammonia water, 20 mL of ethanol, and 45 mL of deionized water are mixed, stirred at 25° C. for 20 min, 2 g of polyethylene glycol is added, a mixed solution of 2.5 g of dopamine hydrochloride and 5 mL of deionized water is added, 0.5 g of composite fiber nanocrystals, 5 g of modified β-cyclodextrin, and 10 mL of deionized water is added, and ultrasonic stirring is performed for 30 min to obtain the antifouling impregnation liquid;
[0066] The preparation of the composite fiber nanocrystal comprises the following steps:
[0067] 1) 0.1 g of fiber nanocrystals and 100 mL of deionized water were mixed, ultrasonically treated for 30 min, heated to 30 °C, 3 mL of titanium tetrachloride was added, and the mixture was kept warm for 40 min. The mixture was cooled, centrifuged, washed, dried, and ground to obtain modified fiber nanocrystals.
[0068] 2) Mix 2.2 g of hydroquinone acrylamide, 5 g of composite fiber nanocrystals, and 20 mL of N,N-dimethylformamide, heat to 102 °C, stir for 1 h, add 1.8 g of 3-acrylamidophenylboronic acid, keep warm for 10 min, add 0.04 g of azobisisobutyronitrile, keep warm for 3 h, and obtain composite fiber nanocrystals;
[0069] The preparation of the modified β-cyclodextrin comprises the following steps:
[0070] (1) 17.2 g of β-cyclodextrin and 200 mL of 1% NaOH solution were mixed, 2.9 g of p-toluenesulfonyl chloride and 11 mL of acetonitrile were added, stirring was continued for 3 h, vacuum filtered, the pH of the solution was adjusted to 2, and the solution was kept at 3 °C for 12 h, vacuum filtered, dried, and recrystallized. Boiling distilled water was added until dissolved, cooled, vacuum filtered, and dried to obtain mono-(6-O-p-methylbenzenesulfonyl)-β-cyclodextrin;
[0071] (2) Mix 4 g of mono-(6-O-toluenesulfonyl)-β-cyclodextrin and 0.7 mol of diallylamine, heat to 82 °C in a water bath for 4 h, cool, add 40 mL of methanol and 240 mL of acetonitrile, filter and dry to obtain vinylated β-cyclodextrin;
[0072] (3) 5 g of vinylated β-cyclodextrin, 1 g of hydroquinone acrylamide, and 20 mL of N,N-dimethylformamide were mixed, kept warm for 2 h, 0.03 g of azobisisobutyronitrile was added, and the temperature was raised to 80 °C and kept warm for 2 h to obtain modified β-cyclodextrin;
[0073] The preparation of the hydroquinone acrylamide comprises the following steps:
[0074] 2mmol hydroquinone, 1mmol N-hydroxymethyl acrylamide, and 500mL anhydrous ethanol were mixed, heated to 35°C, 30mL concentrated sulfuric acid was added, the mixture was kept warm for 8 days, allowed to stand for 1 day, filtered and washed until neutral, recrystallized with anhydrous ethanol for 5 times, and dried to obtain hydroquinone acrylamide;
[0075] S3: The pretreated ceramic membrane is transferred to an anti-fouling impregnation solution, ultrasonically vibrated, and dried to obtain a high-flux, anti-fouling inorganic special membrane.
[0076] Comparative Example 1: Taking Example 3 as the control group, the composite fiber nanocrystals were replaced with fiber nanocrystals, and the other processes were normal.
[0077] Comparative Example 2: Taking Example 3 as the control group, β-cyclodextrin was used to replace the composite β-cyclodextrin, and the other processes were normal.
[0078] Comparative Example 3: Example 3 was used as a control group, hydroquinone acrylamide was not prepared, and other processes were normal.
[0079] The thickness of the protective layer in the above-mentioned embodiments and comparative examples is 10 μm.
[0080] The preparation of fiber nanocrystals includes the following steps:
[0081] 10 g of bamboo pulp, 0.4 g of TEMPO, 2 g of sodium bromide, and 75 g of a 5% sodium hypochlorite aqueous solution were mixed, the pH value was maintained at 10.3, stirred for 23 h, washed, centrifuged, and dried to obtain fiber nanocrystals.
[0082] Source of raw materials used:
[0083] Ceramic membrane (zirconia membrane, pore size 50 nm): Nanjing Jiuwu High-Tech Co., Ltd.; bamboo pulp: commercially available; TEMPOT106827, polyethylene glycol P103719, dopamine hydrochloride D103111, titanium tetrachloride T432017, 3-acrylamidophenylboronic acid A188951, azobisisobutyronitrile A434183, hydroquinone H108945, triethylamine T103285, N,N-dimethylformamide D111999, β-cyclodextrin C104384, p-toluenesulfonyl chloride T104623, diallylamine D106260, N-hydroxymethylacrylamide N-hydroxymethylacrylamide M108949: Aladdin reagent; ammonia water, ethanol, NaOH solution, sodium hypochlorite, sodium bromide, acetonitrile, methanol, concentrated sulfuric acid, analytical grade: Sinopharm Group reagent.
[0084] Performance test: The inorganic special membranes prepared in the examples and comparative examples were tested;
[0085] Specific flux: Use an ultrafiltration cup to filter the solution in a dead-end filtration method. Filter deionized water at a pressure of 0.01 MPa until the volume of the filtrate per unit time is constant. The pure water flux J W =ΔV / (A·Δt), Δt-filtration time (s), ΔV-volume of filtrate collected within Δt (m 3 ), A- effective filtration area of membrane (m 2 ); specific flux RJ=J W1 / J W2 , J W1 , J W2 Indicates the flux of ceramic membrane before and after modification, (L / (m 2 ∙ h));
[0086] Antibacterial activity: The samples were cut into 1 cm × 1 cm pieces and immersed in a PBS solution with a pH of 7.2. Escherichia coli was inoculated into LB medium and oscillated at a constant temperature of 37°C until the absorbance at 600 nm (OD 600 ) is 0.7, and the concentration of E. coli is 10 9 CFU / mL, centrifuge the bacterial solution, remove the remaining culture medium, resuspend with an equal volume of PBS solution, add 1 mL to the membrane for contact for 3 hours, and perform fluorescence microscopy test. Take the membrane with adsorbed bacteria and wash the surface attached liquid with PBS solution, then use 5 mL of PBS solution for ultrasonic washing for 10 minutes, take 400 µL of washing solution, add 20 µL of acridine orange / ethidium bromide double staining reagent in a dark room, let it stand for 5 minutes, then add the staining solution to the slide, fix it with a coverslip, and transfer it to a fluorescence microscope for observation. Take the above washing solution and count the remaining live bacteria by dilution plate coating method;
[0087] Self-healing property: A scratch with a length of 1 mm, a width of 2 µm, and a depth of 5 µm was made on the surface of the protective layer and placed at 80°C for 24 hours. The self-healing efficiency was (L0-L1) / L0×100%, where L0 is the initial length of the scratch and L1 is the length of the scratch after heat preservation.
[0088] Pollution resistance: Use an ultrafiltration cup to filter the solution in a dead-end filtration mode. Filter the simulated printing and dyeing grade III wastewater at a pressure of 0.01MPa until the filtrate volume per unit time is constant. Prepare the wastewater into simulated printing and dyeing grade III wastewater, that is, wastewater with a COD value of 500mg / L and a BOD value of 100mg / L. Use a COD ammonia nitrogen dual parameter measuring instrument to test the COD value of the wastewater before and after filtration, and calculate the degradation rate of the COD value: η=(X0-Xi) / X0×100%; X0 is the COD value of the wastewater before degradation, mg / L; Xi is the COD value of the wastewater after degradation, mg / L. The same inorganic special membrane was tested for 15 cycles; the results are shown in Table 1;
[0089] Table 1
[0090]
[0091] The present invention provides a high-flux, anti-pollution inorganic special membrane and its preparation process, including a ceramic membrane and a protective layer formed on the surface of the ceramic membrane by a protective impregnation liquid, so that the prepared inorganic special membrane has high flux and a self-repairing green, antibacterial and anti-pollution surface.
[0092] By comparing Example 3 with Comparative Example 1 and Comparative Example 3, it can be seen that the present invention selects bio-based raw materials dopamine hydrochloride, fiber nanocrystals, and β-cyclodextrin as raw materials to construct a protective impregnation solution; in order to give the ceramic membrane the ability to photodegrade pollutants, titanium tetrachloride is used to in situ generate titanium dioxide on the surface of the fiber nanocrystals to obtain modified fiber nanocrystals, and in order to improve the uniformity of dispersion of the fiber nanocrystals in the protective impregnation solution, hydroquinone acrylamide with anti-fouling and antibacterial effects is attached to the modified fiber nanocrystals using the hydroxyl groups on their surfaces, and then 3-acrylamide phenylboronic acid is further grafted using a free radical reaction to obtain composite fiber nanocrystals, and the boric acid groups on the composite fiber nanocrystals and the polyethylene glycol in the protective impregnation solution have dynamic borate ester bonds to give the protective layer a certain self-repairing ability, thereby improving the long-lasting antibacterial and anti-fouling properties of the inorganic special membrane.
[0093] By comparing Example 3 with Comparative Examples 2 and 3, it can be seen that β-cyclodextrin is introduced into the protective impregnation liquid to further improve the stability of the protective layer. In order to improve the uniformity of the dispersion of β-cyclodextrin in the protective impregnation liquid, a multiple interpenetrating cross-linked network of β-cyclodextrin, polydopamine, and polyethylene glycol is constructed to further improve the self-repairing ability of the protective layer and the adhesion of the protective impregnation liquid to the ceramic membrane. Using β-cyclodextrin as a raw material, mono-(6-O-p-methylbenzenesulfonyl)-β-cyclodextrin is synthesized, and then it is vinylized with diallylamine to obtain vinylated β-cyclodextrin, and then free radical reaction is used to continue to graft hydroquinone acrylamide with anti-fouling and antibacterial effects to give it antibacterial and anti-fouling permanence, thereby significantly improving the anti-fouling and separation selectivity of the inorganic special membrane and broadening the scope of use of the inorganic special membrane.
[0094] The above descriptions are only embodiments of the present invention and are not intended to limit the patent scope of the present invention. All equivalent structural changes made using the present invention specification under the inventive concept of the present invention, or direct / indirect applications in other related technical fields, are included in the patent protection scope of the present invention.
Claims
1. A process for preparing a high-flux, anti-pollution inorganic special membrane, characterized in that: The following steps are involved: S1: washing the ceramic membrane to obtain a pretreated ceramic membrane; S2: preparing a protective impregnation solution using ammonia water, ethanol, deionized water, polyethylene glycol, modified β-cyclodextrin, dopamine hydrochloride, and composite fiber nanocrystals; S3: transferring the pretreated ceramic membrane into a protective impregnation solution, ultrasonically vibrating, and drying to obtain a high-flux, anti-pollution inorganic special membrane; The preparation of the composite fiber nanocrystal comprises the following steps: 1) Mix the fiber nanocrystals and deionized water, perform ultrasonic treatment for 20-30 minutes, heat to 20-30°C, add titanium tetrachloride, keep warm for 40-60 minutes, cool, centrifuge, wash, dry and grind to obtain modified fiber nanocrystals; 2) Mix hydroquinone acrylamide, modified fiber nanocrystals and N,N-dimethylformamide, heat to 98-102°C, stir for 1-2h, add 3-acrylamidophenylboronic acid, keep warm for 8-10min, add azobisisobutyronitrile, keep warm for 2-3h, and obtain composite fiber nanocrystals; The preparation of the modified β-cyclodextrin comprises the following steps: (1) β-cyclodextrin and NaOH solution were mixed, p-toluenesulfonyl chloride and acetonitrile were added, stirring was continued for 2-3 hours, vacuum-filtered, the pH of the solution was adjusted to 2, and the solution was kept warm at 3°C for 10-12 hours, vacuum-filtered, dried, and recrystallized. Boiling distilled water was added until dissolved, cooled, vacuum-filtered, and dried to obtain mono-(6-O-p-methylbenzenesulfonyl)-β-cyclodextrin; (2) Mix mono-(6-O-toluenesulfonyl)-β-cyclodextrin and diallylamine, heat to 78-82°C in a water bath for 4-5 hours, cool, add methanol and acetonitrile in sequence, filter, and dry to obtain vinylated β-cyclodextrin; (3) vinylated β-cyclodextrin, hydroquinone acrylamide and N,N-dimethylformamide are mixed, kept warm for 1-2 hours, azobisisobutyronitrile is added, and the temperature is raised to 60-80°C and kept warm for 2-3 hours to obtain modified β-cyclodextrin; The preparation of the hydroquinone acrylamide comprises the following steps: Mix hydroquinone, N-hydroxymethyl acrylamide and anhydrous ethanol, heat to 30-35°C, add concentrated sulfuric acid, keep warm for 8 days, let stand for 1 day, filter and wash until neutral, recrystallize with anhydrous ethanol 3-5 times, and dry to obtain hydroquinone acrylamide.
2. The process for preparing a high-flux, anti-pollution inorganic special membrane according to claim 1, characterized in that: The working conditions of ultrasonic oscillation are: time is 10-15min.
3. The process for preparing a high-flux, anti-pollution inorganic special membrane according to claim 1, characterized in that: The preparation of the protective impregnation liquid includes the following steps: mixing ammonia water, ethanol and deionized water, stirring at 18-25°C for 20-30 minutes, adding polyethylene glycol, adding a mixed solution of dopamine hydrochloride and deionized water, adding a mixed solution of composite fiber nanocrystals, modified β-cyclodextrin and deionized water, and ultrasonically stirring for 20-30 minutes to obtain the protective impregnation liquid.
4. The process for preparing a high-flux, anti-pollution inorganic special membrane according to claim 3, characterized in that: The mass ratio of polyethylene glycol, dopamine hydrochloride, composite fiber nanocrystals and modified β-cyclodextrin is 2:2.5:(0.3-0.5):
5.
5. The process for preparing a high-flux, anti-pollution inorganic special membrane according to claim 1, characterized in that: In the preparation of the composite fiber nanocrystals, the mass ratio of hydroquinone acrylamide, composite fiber nanocrystals, and 3-acrylamidophenylboric acid is 2.2:5:1.
8.
6. The process for preparing a high-flux, anti-pollution inorganic special membrane according to claim 1, characterized in that: In the preparation of modified β-cyclodextrin, the mass ratio of vinylated β-cyclodextrin and hydroquinone acrylamide is 5:
1.
7. A high-flux, anti-pollution inorganic special membrane, characterized in that: Prepared according to the preparation process according to any one of claims 1 to 6.
